Digital Ethnography of Students’ Communication on WhatsApp: An Empirical Study of Native Bantenese - kheryadi, kheryadi; Afif Suaidi (STAIN Majene, 2023)
This study delves into understanding the distinctive communication behavior within a specific speech community established on WhatsApp. Employing communication ethnography and utilizing Dell Hymes' Speaking Model for analysis, the research employs observation techniques and in-depth interviews for data collection. Findings reveal that speech events primarily unfold within designated group accounts, centering on common topics. Notably, not all community members actively engage, and communication encompasses both textual and visual formats, in line with the application's features. Despite adherence to the application's conversational structure, community members demonstrate a robust comprehension of diverse speech forms exchanged within the group. The abstract concludes by underscoring the pedagogical implications of the results, offering insights for comprehending and potentially enhancing communication behaviors in chat applications, contributing to the broader discourse on digital communication